Super-hydrophobic multilayer coatings with layer number tuned swapping in surface wettability and redox catalytic anti-corrosion application - Syed, Junaid Ali (Sci Rep, 2017)
The wetting characteristic of a metal surface can be controlled by employing different coating materials and external stimuli, however, layer number (n) modulated surface swapping between hydrophobicity and hydrophilicity in a multilayer structure to achieve prolonged anti-corrosion ability was not taken into consideration. In this study, we proposed a layer-by-layer (LbL) spin assembled polyaniline-silica composite/tetramethylsilane functionalized silica nanoparticles (PSC/TMS-SiO(2)) coating with the combined effect of super-hydrophobicity and enhanced anti-corrosion ability. Interestingly, the hierarchical integration of two coating materials with inherently different surface roughness and energy in a multilayer structure allows the wetting feature to swap from hydrophobic to hydrophilic state by modulating n with decreasing hydrophilicity. The samples with odd n (TMS-SiO(2) surface) are hydrophobic while the samples with even n (PSC surface) exhibits the hydrophilic character. The TMS-SiO(2) content was optimized to achieve super-hydrophobic coating with significantly high water contact angle (CA) 153° ± 2° and small sliding angle (SA) 6° ± 2°. Beside its self-cleaning behavior, the electro-active PSC/TMS-SiO(2) coating also exhibits remarkably enhanced corrosion resistance against aggressive media. The corrosion resistance of the coating was remained stable even after 240 h of exposure, this enhancement is attributed to super-hydrophobicity and anodic shift in corrosion potential.